Toothpastes containing herbal medicines in their composition and their benefits: a literature review (Research, Society and Development, 2022)
Toothpaste are personal hygiene products used in the prevention and treatment of diseases prevalent in the oral cavity, such as tooth decay and periodontal diseases. This study is a literature review, with a narrative character about toothpastes containing herbal medicines in their composition and their reported benefits. The literature review was carried out with articles published in Portuguese and English, found between the months of January and August 2021 in the online databases of Scielo, BVS, PubMed and Google Scholar. With the selected information, a narrative analysis was carried out, relating the dentifrices and their components as well as the properties of each herbal medicine. 22 articles were selected between the years 1999 and 2021. The addition of herbal medicines to toothpastes enhances their action. The usual indications of herbal medicines are associated with the treatment of infections, inflammation, toothache and healing processes, among others. The correct use of herbal medicines provides a series of benefits, since natural products are easily accessible, have low toxicity and scientifically proven biocompatibility. The herbal medicines present in toothpastes are viable alternatives for the control and treatment of oral diseases, especially dental biofilm.